ANTI FUZZY SUBSEMIRING - Saman Abdurrahman; Cendikia Hira; Alya Hanifah Arif (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
When the first operation’s inverse axiom is deleted from the ring, an algebraic structure, the semiring, is generated. Subsemiring is one of the subjects covered in semiring. The concepts of fuzzy subsemiring, anti subsemiring fuzzy semiring, and complement are introduced in this paper. In addition, the anti-subsemiring fuzzy semiring, a wedge, or a combination of two or more fuzzy anti-subsemiring associated with a non-empty subset of the semiring whose membership criteria are defined by the membership value of the zero elements will be discussed.